A case of breakthrough infection with SARS-CoV-2 Delta derivative and reinfection with Omicron variant in a fully vaccinated health care professional. Issue 1 (July 2022) - Pandit, Priyanka; Bhatt, Puneet; Sahay, Rima R.; Joshi, Yash; Patil, Deepak Y.; Yadav, Pragya D.
Highlights: Primary infection, breakthrough and reinfection in health care professional. Breakthrough infection was found to occur due to Delta derivative. Omicron was identified to be the cause of reinfection. IgG antibody titres were low even post reinfection.